2016
DOI: 10.1016/j.jhealeco.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Provider practice style and patient health outcomes: The case of heart attacks

Abstract: When a patient arrives at the Emergency Room with acute myocardial infarction (AMI), the provider on duty must quickly decide how aggressively the patient should be treated. Using Florida data on all such patients from 1992 to 2014, we decompose practice style into two components: The provider's probability of conducting invasive procedures on the average patient (which we characterize as aggressiveness), and the responsiveness of the choice of procedure to the patient's characteristics. We show that within ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 18 publications
6
66
1
Order By: Relevance
“…For example, discussing the use of invasive cardiac procedures, Currie, MacLeod, and Van Parys (2016) explain that if "surgery becomes generally safer over time," and thus less costly to conduct, "then it may make sense to use aggressive procedures on more marginal patients over time." Prior research has found that physicians utilize procedures based on ease and safety of use.…”
Section: The General Impact Of Justification On Test Usementioning
confidence: 99%
See 4 more Smart Citations
“…For example, discussing the use of invasive cardiac procedures, Currie, MacLeod, and Van Parys (2016) explain that if "surgery becomes generally safer over time," and thus less costly to conduct, "then it may make sense to use aggressive procedures on more marginal patients over time." Prior research has found that physicians utilize procedures based on ease and safety of use.…”
Section: The General Impact Of Justification On Test Usementioning
confidence: 99%
“…There are two manners in which justification could decrease US use: physicians could be less "aggressive" in US use for all patients in general, or they could be more "responsive" to clinical need and reduce usage primarily for marginalprobability patients (Currie et al, 2016). Abdominal USs are the preferred modality for only certain medical conditions (please see Section 4 and Appendix B for more detail) (American College of Emergency Physicians, 2008).…”
Section: Mechanisms: the Moderating Effect Of Patient Conditionmentioning
confidence: 99%
See 3 more Smart Citations